KONTRIBUSI KEKUATAN OTOT LENGAN, KELENTUKAN PINGGANG, DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN PUKULAN LOB PADA MAHASISWA BULUTANGKIS UNTARA - Yudhi Esa Saputra; Siti Juabedah; Ghalih Kurniawan (Universitas Tangerang Raya, 2022)
The problem of badminton athletes at the Universitas Tangerang Raya caused by the declining achievement factor experienced by athletes. The purpose of this study was to determine the contribution of arm muscle strength, waist flexibility, and hand-eye coordination to the lob ability of badminton athletes. The population of this study amounted to 59 people. The sampling technique was taken by